Records of Ibisbill Ibidorhyncha struthersii in the Bhagirathi River, Harsil, Uttarakhand, India - Sinha, Ankita; Tanvi; Adhikari, B. S.; Ramesh, K. (Journal of the Bombay Natural History Society (JBNHS), 2014)
No abstract.